Analysis of Zero-Gravity Unloading Positions for 2-DOF Space Manipulators - Liu, Mingtao; Zhang, Qi; Chen, Gang; Bai, Jiaxuan (Journal of Research in Science and Engineering, 2026)
The gravity unloading mechanism using the air flotation method is a device that supports aerospace equipment by ejecting high-pressure gas from the bottom air foot to counteract most or all of the gravity in aerospace simulations. Due to the structural characteristics of the aviation manipulator, such as a large length-to-diameter ratio, light weight, and long cantilever, the unloading position is a critical factor affecting the unloading rate under the influence of gravity. Therefore, using a manipulator demonstration platform as the research object, the multi-objective optimization of the manipulator's unloading position is conducted. The rigid deformation of the manipulator serves as the optimization objective. Meanwhile, the additional bending moment, rotation angle, bending stress, and interference issues between the manipulator and other equipment are considered constraints for multi-objective optimization. The optimal unloading position is determined by comparing two different algorithms. The strain simulation of the manipulator under the optimal unloading position is to analyze the deformation of the end of the manipulator.